Effects of Al content on pore structures of porous TiVAlC ceramics by reactive synthesis. Issue 6 (15th March 2021) - Zou, Haoran; Li, Xide; Zhang, Chuo; Li, Bin; Liu, Yuzuo; Yang, Xuejin; Xiong, Lieqiang; Zheng, Xiao; Yang, Junsheng
Abstract: Porous TiVAlC ceramics were successfully prepared using mixed powders of TiH2, V, Al, and graphite with a molar ratio of 1/1/n/1 (n, 0.9–1.7 in 0.2 increments). Systematic experimental results showed the significant effects of Al content on the pore structure of these TiVAlC ceramics. With increased Al content, from 0.9 to 1.3 mol, pore sizes and viscous permeability coefficients of these materials gradually decreased and porosity showed an increasing tendency. As the Al content increased to 1.7 mol, the pore sizes, viscous permeability coefficients, and porosities all varied in the opposite direction. In addition, the reasons for these phenomena and the mechanism of pore forming in these ceramics were explored. The present study offered a significant reference for subsequent research into the fabrication of quaternary and multi-element porous alloys/ceramics. Highlights: Porous TiVAlC ceramics were prepared by a reactive synthesis method. The pore structure parameters can be changed by adjusting the Al content. The Pore forming mechanism of porous TiVAlC ceramics was systematically analyzed.